2019
DOI: 10.1080/08870446.2019.1587441
|View full text |Cite
|
Sign up to set email alerts
|

Socioemotional selectivity and psychological health in amyotrophic lateral sclerosis patients and caregivers: a longitudinal, dyadic analysis

Abstract: Objective-Socioemotional selectivity theory predicts that as the end of life approaches, goals and resources that provide immediate, hedonic reward become more important than those that provide delayed rewards. The present study tested whether these goal domains differentially affected psychological health in the context of marital dyads in which one partner had been diagnosed with amyotrophic lateral sclerosis (ALS), a life-limiting disease. Design-ALS patients (N = 102) being treated in 3 multidisciplinary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 47 publications
1
10
0
2
Order By: Relevance
“…Previous reports showed that the majority of ALS patients and caregivers experienced the loss of participation in regular activities, feelings of being “homebound” and disconnected from the community as disease progress 28 . These changes in social connections and reduced social activities 7,28 were associated with feelings of loneliness, poor QoL, severe depressive mood, and emotional distress 8,29 . In our sample, regression analyses documented the pivotal role of loneliness, over age and disease stage, on depressive symptoms of ALS patients (Table 4).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous reports showed that the majority of ALS patients and caregivers experienced the loss of participation in regular activities, feelings of being “homebound” and disconnected from the community as disease progress 28 . These changes in social connections and reduced social activities 7,28 were associated with feelings of loneliness, poor QoL, severe depressive mood, and emotional distress 8,29 . In our sample, regression analyses documented the pivotal role of loneliness, over age and disease stage, on depressive symptoms of ALS patients (Table 4).…”
Section: Discussionsupporting
confidence: 58%
“…28 These changes in social connections and reduced social activities 7,28 were associated with feelings of loneliness, poor QoL, severe depressive mood, and emotional distress. 8,29 In our sample, regression analyses documented the pivotal role of loneliness, over age and disease stage, on depressive symptoms of ALS patients (Table 4). The P-values of chi-squared tests are reported.…”
Section: Neurobehavioral Changes and Loneliness In Alsmentioning
confidence: 81%
“…A preocupação com aspectos financeiros depende do estágio da doença, pacientes em estágio inicial aumentam a preocupação financeira, entretanto o avanço da doença e a sensação de proximidade da morte influencia, diminuindo o valor atribuído aos recursos financeiros. 20 O apoio social funcional é um conceito subjetivo, que diz respeito às percepções do indivíduo sobre a sua própria disponibilidade de suporte. Os dados indicam que para a amostra estudada, há uma maior percepção da existência de pessoas em sua rede social que lhes amem (Apoio afetivo) e com quem podem ter momentos de prazer e relaxamento (Interação Social), e apoiar-lhes com medidas práticas (Apoio Material).…”
Section: Discussionunclassified
“…25 A literatura evidencia que pacientes com ELA e seus cônjuges não diferem em relação aos níveis de percepção de solidão, o que reflete em preocupação com a adequação das relações sociais próximas. 20 Um corpo moderado de evidências demonstra que cuidadores, que experimentam sintomas depressivos, são mais propensos a apresentar alta sobrecarga. 18 Apesar da escassez de estudos sobre o apoio social nos cuidadores dos pacientes com ELA, e de nossa pesquisa não ter utilizados avaliações específicas para mensuração de sintomas depressivos.…”
Section: Discussionunclassified
“…Carers are also known to be at higher risk of loneliness compared to the general population [ 28 , 29 ], but there has been limited research looking at the experience of informal carers of people with mental health problems. We therefore looked at the potential association between experiences of caring and levels of loneliness, measured using the brief 3-item version of the University of California, Los Angeles (UCLA-3) loneliness scale [ 30 ].…”
Section: Methodsmentioning
confidence: 99%